Design of internal power supply circuit for mining intrinsic safety broadcasting system equipment - Dedong ZOU; Chengdong LI (Meikuang Anquan)
The mining intrinsic safety broadcasting system equipment has the characteristics of unbalanced load current and high power consumption. In response to the problems of high start-up impulse current, short power supply distance, unreliable voltage reducing devices, and poor electromagnetic interference resistance of equipment, a safe, reliable, and stable internal power supply circuit for intrinsically safe broadcasting system equipment has been designed through the study of the protection mechanism of intrinsically safe power supply, the analysis of the load characteristics and electromagnetic interference factors of intrinsically safe broadcasting system equipment, and combined with the standard requirements of intrinsic safety protection equipment. The circuit has linear suppression of impulse current, balanced working current, and electromagnetic compatibility functions. Detailed introduction of the composition and working principles of electromagnetic compatibility unit, impulse current suppression unit, load balancing unit, and voltage reduction unit, and in-depth explanation of two key technologies: slow start and heavy load current balancing. The focus is on the generation, impact, suppression methods, and calculation of circuit parameters for impulse current. Practical application has proven that the designed power supply circuit fully meets the requirements of intrinsic safety and the need for stable and reliable equipment operation.